A Phase 1 Study of ABI‐009 (Nab‐sirolimus) in Combination With Temozolomide and Irinotecan in Pediatric Patients With Recurrent or Refractory Solid Tumors, Including CNS Tumors—A Children's Oncology Group Pediatric Early Phase Clinical Trial Network Study ADVL1514 - Stuart L. Cramer; Alyssa Terry Reddy; Charles Gene Minard; Stephan Voss; Elizabeth Fox; Xiaowei Liu; Kristina Denic; Joel M. Reid; Brenda J. Weigel (Cancer Medicine)
ABSTRACT Background Nab‐sirolimus (ABI‐009, nab‐rapamycin; Aadi Bioscience Inc. [Aadi]) is a human albumin‐bound form of sirolimus nanoparticles, a potent mTOR inhibitor. This phase I trial was conducted to define dose‐limiting toxicities (DLT), maximum tolerated or recommended phase II dose (MTD/RP2D), and pharmacokinetics of Nab‐sirolimus in combination with temozolomide and irinotecan. Methods Using a rolling 6 design, Nab‐sirolimus was administered intravenously (IV) on days (D) 1 and 8 of cycle (C) 1. In subsequent cycles, Nab‐sirolimus was administered D1 and D8 in combination with temozolomide (125 mg/m2/dose, maximum 250 mg/dose) and irinotecan (90 mg/m2/dose) orally, daily on D1–5. Cycle duration was 21 days. Three dose levels (DL) of Nab‐sirolimus were investigated (DL1: 35 mg/m2/dose, DL‐1: 20 mg/m2/dose, and DL‐2: 15 mg/m2/dose). The observation period for estimating the MTD/RP2D was defined by cycles 1 and 2. Results Thirty‐three patients were enrolled, 32 were eligible. Dose determination included 17 evaluable patients, median (range) age 12 (2–20) years and six additional patients were enrolled (four evaluable for toxicity) on a pharmacokinetic cohort. C1 or C2 DLTs were primarily thrombocytopenia including 2/5 patients at DL1, 2/6 patients at DL‐1, and 1/6 patients at DL‐2. One patient (DL1) with Ewing Sarcoma had a partial response and remained on study for 35 cycles. Rapamycin clearance was dose dependent. Irinotecan clearance and its active metabolite SN‐38 exposure were not affected by coadministration with Nab‐sirolimus. Conclusion The MTD for Nab‐sirolimus was 15 mg/m2/dose IV on D1 and D8 in combination with temozolomide 125 mg/m2/dose and oral irinotecan 90 mg/m2/dose daily for 5 days during 21D cycles. Trial Registration ClinicalTrials.gov identifier NCT02975882